Extension of the Thoracic Spine Sign: A New Sonographic Marker of Pleural Effusion. (12th August 2015) - Dickman, Eitan; Terentiev, Victoria; Likourezos, Antonios; Derman, Anna; Haines, Lawrence
Abstract : Objectives: Dyspnea is a common emergency department (ED) condition, which may be caused by pleural effusion and other thoracic diseases. We present data on a new sonographic marker, the extension of the thoracic spine sign, for diagnosis of pleural effusion. Methods: In this prospective study, we enrolled a convenience sample of undifferentiated patients who underwent computed tomography (CT) of the abdomen or chest, which was performed as part of their emergency department evaluations. Patients underwent chest sonography to assess the utility of the extension of the thoracic spine sign for diagnosing pleural effusion. The point‐of‐care sonographic examinations were performed and interpreted by emergency physicians who were blinded to information in the medical records. Sonographic results were compared to radiologists' interpretations of the CT results, which were considered the criterion standard. Results: Forty‐one patients were enrolled, accounting for 82 hemithoraces. Seven hemithoraces were excluded from the analysis due to various limitations, leaving 75 hemithoraces for the final analysis. The median time for completion of the sonographic examination was 3 minutes. The sensitivity and specificity for extension of the thoracic spine were 73.7% (95% confidence interval [CI], 48.6%–89.9%) and 92.9% (95%CI, 81.9%–97.7%), respectively. Overall, there were 5 hemithoraces with false‐negative results when using the extension sign. Of those 5 cases, 4 were found to have trace pleural effusions on CT. When trace pleural effusions were excluded in a subgroup analysis, the sensitivity and specificity of extension of the thoracic spine were 92.9% (95% CI, 64.2%–99.6%) and 92.9% (95% CI, 81.9%–97.7%). Conclusions: We found the extension of the thoracic spine sign to be an excellent diagnostic tool for clinically relevant pleural effusion.